Leading Agricultural Subsectors in South Sumatra Province Before and During The COVID-19 Pandemic - Muhammad Aris Pujiyanto; Dwidjono Hadi Darwanto; Jangkung Handoyo Mulyo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2022)
The COVID-19 pandemic that started in Wuhan, China, in December 2019 has resulted a very fatal health problems in global history, including for the State of Indonesia, which was confirmed that the first case of COVID-19 appeared on March 2, 2020. The COVID-19 pandemic not only having an impact on the health sector, the economy, international trade, industry but also having a negative impact on the agricultural sector, so that the production and productivity of the agricultural sector during the COVID-19 pandemic experienced a significant decline. So it is necessary to conduct more in-depth research to find out how much impact the COVID-19 pandemic has on leading agricultural sub-sectors in South Sumatra Province. This study aims to determine the leading agricultural sub-sector before and during the COVID-19 pandemic in South Sumatra Province. This study uses secondary data in 2010-2021. The analysis applied in this study is the analysis of Location Quotient (LQ), Dynamic Location Quotient (DLQ), and a combination of analysis of Location Quotient (LQ) and Dynamic Location Quotient (DLQ). The plantation crops sub-sector and the forestry sub-sector are the base sectors. The food crops sub-sector, horticultural crop sub-sector, livestock sub-sector, and forestry sub-sector have a faster growth rate when compared to the same sub-sector at the national level. Only the forestry sub-sector is included in the classification of the leading sub-sector.